Hi‐C scaffolded short‐ and long‐read genome assemblies of the California sea lion are broadly consistent for syntenic inference across 45 million years of evolution. (27th June 2021) - Peart, Claire R.; Williams, Christina; Pophaly, Saurabh D.; Neely, Benjamin A.; Gulland, Frances M. D.; Adams, David J.; Ng, Bee Ling; Cheng, William; Goebel, Michael E.; Fedrigo, Olivier; Haase, Bettina; Mountcastle, Jacquelyn; et al.
Abstract: With the advent of chromatin‐interaction maps, chromosome‐level genome assemblies have become a reality for a wide range of organisms. Scaffolding quality is, however, difficult to judge. To explore this gap, we generated multiple chromosome‐scale genome assemblies of an emerging wild animal model for carcinogenesis, the California sea lion ( Zalophus californianus ). Short‐read assemblies were scaffolded with two independent chromatin interaction mapping data sets (Hi‐C and Chicago), and long‐read assemblies with three data types (Hi‐C, optical maps and 10X linked reads) following the "Vertebrate Genomes Project (VGP)" pipeline. In both approaches, 18 major scaffolds recovered the karyotype (2 n = 36), with scaffold N50s of 138 and 147 Mb, respectively. Synteny relationships at the chromosome level with other pinniped genomes (2 n = 32–36), ferret (2 n = 34), red panda (2 n = 36) and domestic dog (2 n = 78) were consistent across approaches and recovered known fissions and fusions. Comparative chromosome painting and multicolour chromosome tiling with a panel of 264 genome‐integrated single‐locus canine bacterial artificial chromosome probes provided independent evaluation of genome organization. Broad‐scale discrepancies between the approaches were observed within chromosomes, most commonly in translocations centred around centromeres and telomeres, which were better resolved in the VGP assembly. Genomic and cytological approaches agreed on near‐perfect synteny of the X chromosome, and in combination allowed detailed investigation of autosomal rearrangements between dog and sea lion. This study presents high‐quality genomes of an emerging cancer model and highlights that even highly fragmented short‐read assemblies scaffolded with Hi‐C can yield reliable chromosome‐level scaffolds suitable for comparative genomic analyses.